A post-mortem toxicological investigation: Understanding the role of drugs of abuse in violent fatalities in Cape Town, South Africa - Auckloo, Marie Belle Kathrina Mendoza (Division of Forensic Medicine and Toxicology, 2016)
Violence and resulting injuries are critical health burdens worldwide, accounting for the death of millions of individuals annually. The literature reports an association between drug use and violence, providing data indicating that the use of psychoactive substances increases the risk of morbidity and mortality due to violent acts. South Africa has a long history of violence, with one of the highest rates of recorded violence- and injury-related deaths in the world. This is complicated by an increase in illicit substance use and abuse, particularly in the Cape Town Metropole, located within the Western Cape Province. The use of toxicological findings from victims of violent death (homicides, suicides, and accidents) to examine community-specific drug-related violence is slowly increasing in different parts of the world. In South Africa, however, monitoring drug trends in violent fatalities using toxicological analysis is uncommon, and hence drug toxicology of violent-related fatalities is limited. Divided into three contextual sections, this research study focuses on the post-mortem toxicology of violent deaths in a South African setting. The first section provides a general idea of the research problem and an initial development of the investigation process. The second section provides a theoretical basis for performing routine toxicological analyses in deaths due to violence, reports important research work conducted in the field worldwide, and emphasizes the need to monitor toxicological data derived from violent fatalities in Cape Town, South Africa. The last section, in the form of a manuscript, presents the overall research study including the methodology, outcomes, and concluding findings in a concise and illustrative manner. The primary aim of this pilot study was to investigate the prevalence and characteristics of illicit substances in violent fatalities (homicides, suicides, and accidents) of the Salt River mortuary in Cape Town, South Africa. The objectives were to conduct a comprehensive drug toxicology analysis to generate qualitative and comparative data from the aforementioned cases. In addition, this study investigated the dynamics between psychoactive substance use and violent deaths in terms of toxicological trends, and the demographics and circumstances of death of the victim. Lastly, the author discusses potential qualitative associations between illicit substances and violence-related deaths in a South African setting, and provide suggestions for future toxicological analyses in these fatalities.